Fulgencio Batista : The Making of a Dictator - Argote-Freyre, Frank (Book collections on Project MUSE., 2006)
Second only to Fidel Castro, Fulgencio Batista is the most controversial leader in modern Cuban history. And yet, until now, there has been no objective biography written about him. In this book, the first of two volumes, Frank Argote-Freyre provides a full and balanced portrait of this historically shadowed figure. Drawing on an extensive review of Cuban newspapers, government records, memos, oral history interviews, and a selection of Batista's personal documents, Argote-Freyre moves beyond simplistic caricatures to uncover the real man-one with strengths and weak.